2019
DOI: 10.1111/scd.12353
|View full text |Cite
|
Sign up to set email alerts
|

Dental development in a sample of South African HIV‐positive children

Abstract: Aims While oral soft tissue manifestations associated with HIV‐infection in children are well documented, few studies have investigated the dental development of this group. The aim of this study was to assess dental development in a sample of HIV‐positive children in comparison with an age‐matched HIV‐negative control group. Methods and results The sample comprised 44 HIV‐positive children and 44 HIV‐negative children matched for age, gender, and ethnicity. An orthopantomograph (OPG) of each patient was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Although the results showed a slight delay in dental development in the HIV group, the difference was not statistically significant. These results were supported by those of other studies 1,4 . In the current research, the overall mean difference between the chronological age and the estimated dental age was 0.16 years for the HIV-infected males (p = 0.435) and 0.05 years for the HIV-infected females (p = 0.785).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although the results showed a slight delay in dental development in the HIV group, the difference was not statistically significant. These results were supported by those of other studies 1,4 . In the current research, the overall mean difference between the chronological age and the estimated dental age was 0.16 years for the HIV-infected males (p = 0.435) and 0.05 years for the HIV-infected females (p = 0.785).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, no significant difference was detected between the chronological age and the dental age in the HIV and control groups (p > 0.05). Rafael Boschetti de Souza, et al, and Fadi Titinchi, et al, also revealed no significant difference between HIV patients and the control group concerning dental age 1,4 . However, Sibelle Buonora, et al, and M. Trigueiro, et al, a delay in the dental age of HIVinfected children have been reported 20,22 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations